Proccedings of International Scientific Conference "BALTTRIB 2017" 2017
DOI: 10.15544/balttrib.2017.08
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Properties of Non-Tungsten Electro-Spark Coatings on High Speed Steel

Abstract: In this work contactless local electro spark deposition (LESD), has been used to received wear resistant coatings from hard alloys based of ТiC, TiN, TiCN onto high speed steel HS6-5-2. The influence of the operating electric parameters and the electrode materials on the roughness, thickness, microhardness, phase composition, and on the structure of resulting coatings was studied. The impact of different electrode materials on the quality characteristics, the composition and structure of the resulting coatings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 1 publication
1
8
0
1
Order By: Relevance
“…The study of the general laws and micromechanical properties of the formed layer and their influence on the mechanism and wear kinetics allows to determine ways for controlled management of the operational properties of the treated surfaces and to develop technological variants for ESD. This method is used for deposition of coatings on titanium and its alloys most often at a single pulse energy of 0.1-0.5 J [16][17][18][19][20][21][22][23][24][25][26], with a wide range of layering electrode materials -pure metals, alloys and carbide compositions.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the general laws and micromechanical properties of the formed layer and their influence on the mechanism and wear kinetics allows to determine ways for controlled management of the operational properties of the treated surfaces and to develop technological variants for ESD. This method is used for deposition of coatings on titanium and its alloys most often at a single pulse energy of 0.1-0.5 J [16][17][18][19][20][21][22][23][24][25][26], with a wide range of layering electrode materials -pure metals, alloys and carbide compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium carbide is recommended because of its wide range of homogeneity, high hardness, temperature resistance and wear resistance. [7,13,15,22,23,31,33,34,42,43].…”
Section: Considerations In Selecting the Composition Of The Coating Materialsmentioning
confidence: 99%
“…TiN has the lowest friction coefficient and the highest resistance to wear. Furthermore, it is chemically least active with respect to iron and copper and can be an excellent barrier against adhesion and diffusion wear and is the most common in practice material for applying wear-resistant coatings on metal cutting tools of high-speed steels [13][14][15][21][22][23][41][42][43].…”
Section: Considerations In Selecting the Composition Of The Coating Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electric spark deposition technology is considered as a promising technology in improving the surface wear resistance of agricultural machine in soil with tough components [11]. Penyashki et al [12] studied the wear resistance of TiC, TiN-based cemented carbide electrode composite coatings of high-speed steel by non-contact local electrical spark deposition (LESD) technology. Results suggested that coated HS6-5-2 Steel presented 2.5 times the wear resistance as compared with the bare steel.…”
Section: Introductionmentioning
confidence: 99%